The Effect of Interpersonal on the Use of Traditional Medicine in Hypertension Patients with Health Promotion Model Approach - Ronal Surya Aditya (Journal of Global Pharma Technology, 2020)
ABSTRACT: Hypertension is a disease that requires compliance with drug consumption, but many people are affected by using traditional medicine. Interpersonal influences affect them in the choice of treatment. This study aims to determine the interpersonal influence on traditional drug use in hypertensive patients with a theoretical approach to health promotion models. The subjects of this study were 148 hypertension people in Posyandu, Jenggolo Village, Kepanjen Regency. The design of this research is Cross-Sectional with the sampling technique uses purposive sampling to get a sample of 108 people. Retrieval of data using questionnaire sheets and multiple linear regression statistical tests. The results of the study using multiple linear regression test showed that family support had a B value of 0.111 with sig = 0.036, support of health workers had a value of B 0.156 with sig = 0.028, and peer support had a value of B 0.233 with sig = 0.002. The beta coefficient value on family support is 0.203, health worker support is 0.212, and peer support is 0.297. It can be concluded that the three supporters, namely family, health workers and peers, influence the use of traditional medicine. The most dominant influence in this study was on peer support. The results of this study are expected to provide input for other researchers about providing interventions to peers in patients with hypertension.